Model Materi Ajar KitÄbah Muqayyadah Berbasis CEFR dan Terintegrasi Keterampilan Abad Ke-21 - Setiadi, Samsi; Kamal, Muhammad; Arifah, Fatwa; Ilham, Andri (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2022)
This study aims to develop a CEFR-based model of teaching materials for Kitâbah Muqayyadah and integrated 21st century skills. This research was conducted with a development research approach that started with situation analysis, needs analysis, and the development of learning model design concepts. Based on the results of the situation analysis and needs analysis, the development of a model of Kitâbah Muqayyadah teaching materials based on CEFR and integrated 21st century skills are very much needed. The concept of developing a teaching material model is based on a literature review that produces eight 21st century skills. Meanwhile, the ordering model of the Kitâbah Muqayyadah teaching material, which is a writing skill for beginners, is arranged in eight sequences of material starting from the level of compiling isolated sentences to composing image-assisted discourse. In combining or integrating eight 21st century skills in eight sequences of material, teachers can adapt the learning methods to be applied while considering the objectives of each meeting.